PENDEKATAN KONSELING BEHAVIOR TEKNIK SELF MANAGEMENT DALAM MENCEGAH SISWA KECANDUAN GAME ONLINE - Suryadi, Suryadi; Ritonga, Riski Yusuf; Jannah, Nur; Prafitralia, Anisah; Amrulloh, Abdul Karim (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
The purpose of this study is to examine the implementation of the behavioral counseling approach using self-management techniques in preventing and addressing online game addiction among students at SMA Muhammadiyah 1 Yogyakarta. This research employs a qualitative descriptive method with a case study approach. The population consists of all students at SMA Muhammadiyah 1 Yogyakarta, while the research sample is selected through purposive sampling, involving a total of eight students. Data collection techniques include observation, interviews, and documentation. The results indicate that the behavioral counseling process using self-management techniques in addressing online game addiction among students is conducted according to counseling procedure stages, including problem identification, diagnosis, prognosis, therapy (treatment), and evaluation